Conservação de crustáceos límnicos: efeito da temperatura e pesticidas no metabolismo oxidativo de Aegla longirostri, in situ e ex-situ - Cerezer, Cristina (2021)
Freshwater ecosystems, especially low-order streams, are constantly threatened by the advance of agricultural activities that end up contaminating these places with pesticides and degrading the surrounding vegetation, which can cause deleterious effects on aquatic organisms. In these ecosystems, we find eglid crustaceans that are important shredders and are sensitive to environmental disturbances. Thus, the aim of this thesis was to identify and evaluate how pesticides and abiotic variables affect survival, behavior and oxidative stress in the limnic crustacean Aegla longirostri. In the first chapter, the animals were exposed in situ in four streams (reference site, sites 1, 2, and 3). The reference site is a stream preserved without anthropogenic interference with occurrence of eglids, while the other sites no longer exhibit populations of these animals and are influenced by agricultural activities. The exposures were held bi-monthly from November 2017 to September 2018 and lasted 96 hours. Abiotic parameters were measured and water samples were collected during all exposure days. The biochemical parameters analyzed were muscle acetylcholinesterase (AChE) activity; glutathione S-transferase (GST) activity, lipid peroxidation (TBARS) levels, carbolinated protein (CP) content, non-protein thiols (NPSH) levels, antioxidant capacity against peroxides (ACAP), and reactive oxygen species (ROS) in muscles, gills, and hepatopancreas. We found 24 active pesticide ingredients, the most frequent being Clomazone, Atrazine, and Propoxur. Bentazone was the pesticide found in the greatest amounts. The parameters evaluated in this study, including biochemical biomarkers and abiotic factors measured in water, provided a separation of months depending on environmental conditions. There were differences in activity and levels of biomarkers throughout the year within the same point and in a few months between points. The highest concentration or variety of pesticides associated with extreme abiotic data (very high temperatures) was able to generate increased oxidative stress with high levels of TBARS, and ROS in all tissues, even at high levels of ACAP and NPSH. In chapter 2 the animals were exposed under laboratory conditions at 18°C, 21°C, 24°C, and 26°C for 48 hours, aiming to understand whether temperature alone affects survival rate, biochemical biomarkers and behavioral responses. There were significant changes in biochemical parameters in different tissues and in behavioral tests in A. longirostri. The hepatopancreas was especially affected by the rise in temperature, as demonstrated by the high levels of CP. The AChE activity increased in a temperature-dependent manner in the muscle. The GST activity decreased with increasing temperature in all tissues sampled. With these data, it is intended to alert about the risks of exposure to these environmental conditions, trying to contribute to the preservation of the limnic fauna and especially the eglid crabs, since most species are under some degree of threat. The results obtained in this study indicate that, when evaluating the health of polluted limnic ecosystems through the use of bioindicator organisms, the intrinsic effect of abiotic factors, such as temperature, on biomarkers should be considered.